다문화가족 청소년의 스트레스 수준과 구강건강증상에 관한 연구 - 남궁은정; Eun-jung Namkoong; 김희경; Hee-kyoung Kim; 김선일; Sun-il Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2019)
Objectives: The purpose of this study was to investigate the relationship between stress and oral health symptoms in adolescents in multicultural families. Methods: The data from the 10th Korea Youth Risk Behavior Web-based Survey (KYRBWS) were analyzed using PASW Statistics 18.0 (SPSS Inc., Chicago, IL, USA). A total of 795 adolescents, whose mother or father's home country is not Korea, were selected as the final analysis subjects. Results: There was a correlation between the subject's stress level and oral health symptoms. Toothache was significantly increased 2.474 times (p<0.001) compared to lower stress levels. Gum pain and halitosis were significantly increased by 2.394 times and 1.820 times, respectively, compared with those who had low stress (0.001, 0.008). Conclusions: The results suggest that stress experienced by adolescents in multicultural families affects oral health symptoms. Therefore, it is necessary to identify the stress factors and levels in adolescents belonging to multicultural families whose physical and emotional changes are evident and develop a customized program considering their characteristics.